Efforts to Improve Learning Achievement Theme 3 Objects Around Me Subtheme 1 Morning Activities by Applying Simulation Learning Methods to Students of Grade I Min 3 Jakarta Academic Year 2019/2020 - Yuliatin Yuliatin (International Journal Labs, 2023)
This research is based on the following problems: (a) Does Simulation learning affect Thematic learning achievement in grade I students? (b) How high is the level of mastery of Thematic subject matter with the application of simulation learning methods to grade I, students? The objectives of this study are: (a) To reveal the effect of Simulation learning on Thematic learning achievement in grade I students. (b) Want to know how far the understanding and mastery of Thematic subjects after the application of Simulation learning to grade I, students. This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was Grade I students. The data obtained are in the form of formative test results and observation sheets for teaching and learning activities. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (60%,), cycle II (78%), and cycle III (100%). The conclusion of this study is that Simulation can have a positive effect on the learning motivation of Grade I students, and this learning model can be used as an alternative to Thematic learning.